The Contribution of Leg Explosive Power, Abdominal Muscle Strength, and Balance to the Ability to Kick in the Game of Football - Sudirman, Sudirman (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This study aims to find out whether there is a contribution of leg explosive power, abdominal muscle strength, and balance to the ability to kick in a football game. This study included correlational descriptive research with three independent variables, namely, leg explosive power, abdominal muscle strength and balance, and one dependent variable namely the ability to kick the ball in a football game. The population of this study was students of SMA Negeri 4 Takalar. Through the random sampling technique, a sample of 40 students of SMA Negeri 4 Takalar was selected. Data collection techniques using tests measuring leg explosive power with long jumps, abdominal muscle strength using a stopwatch and balance device using static balance tests and the ability to kick the ball in football games with data analysis techniques used are single and multiple regression analysis which is analyzed using SPSS program computer facilities. At a significant rate of 95% or α= 0.05 Based on data analysis, the results were obtained: (1) There was a contribution of leg explosive power to the ability to kick the ball in a football game, a contribution value of 73.5% was obtained. (2) There is a contribution of abdominal muscle strength to the ability to kick the ball in football games, obtaining a contribution value of 41.7%. (3) There is a balance contribution to the ability to kick the ball in a football game, a contribution value of 29.5% is obtained (4) There is a contribution of leg explosive power, abdominal muscle strength, and balance simultaneously to the speed of the ability to kick the ball in a football game, a contribution value of 87.1% is obtained.